Development of a novel motivational interviewing (MI) informed peer-support intervention to support mothers to breastfeed for longer - Rhiannon Phillips; Lauren Copeland; Aimee Grant; Julia Sanders; Nina Gobat; Sally Tedstone; Helen Stanton; Laura Merrett; Stephen Rollnick; Michael Robling; Amy Brown; Billie Hunter; et al. (BMC, 2018)
Abstract Background Many women in the UK stop breastfeeding before they would like to, and earlier than is recommended by the World Health Organization (WHO). Given the potential health benefits for mother and baby, new ways of supporting women to breastfeed for longer are required. The purpose of this study was to develop and characterise a novel Motivational Interviewing (MI) informed breastfeeding peer-support intervention. Methods Qualitative interviews with health professionals and service providers (n = 14), and focus groups with mothers (n = 14), fathers (n = 3), and breastfeeding peer-supporters (n = 15) were carried out to understand experiences of breastfeeding peer-support and identify intervention options. Data were audio-recorded, transcribed, and analysed thematically. Consultation took place with a combined professional and lay Stakeholder Group (n = 23). The Behaviour Change Wheel (BCW) guided intervention development process used the findings of the qualitative research and stakeholder consultation, alongside evidence from existing literature, to identify: the target behaviour to be changed; sources of this behaviour based on the Capability, Opportunity and Motivation (COM-B) model; intervention functions that could alter this behaviour; and; mode of delivery for the intervention. Behaviour change techniques included in the intervention were categorised using the Behaviour Change Technique Taxonomy Version 1 (BCTTv1). Results Building knowledge, skills, confidence, and providing social support were perceived to be key functions of breastfeeding peer-support interventions that aim to decrease early discontinuation of breastfeeding. These features of breastfeeding peer-support mapped onto the BCW education, training, modelling and environmental restructuring intervention functions. Behaviour change techniques (BCTTv1) included social support, problem solving, and goal setting. The intervention included important inter-personal relational features (e.g. trust, honesty, kindness), and the BCTTv1 needed adaptation to incorporate this. Conclusions The MI-informed breastfeeding peer-support intervention developed using this systematic and user-informed approach has a clear theoretical basis and well-described behaviour change techniques. The process described could be useful in developing other complex interventions that incorporate peer-support and/or MI.